2021
DOI: 10.1111/beer.12411
|View full text |Cite
|
Sign up to set email alerts
|

Ethical human resource management mitigates the positive association between illegitimate tasks and employee unethical behaviour

Abstract: Drawing on social cognitive theory and social information processing theory, we developed a moderated mediation model in which moral disengagement was theorised as a unique mechanism to explain why employees engage in unethical behaviours after performing illegitimate tasks. Ethical human resource management (HRM) was proposed as a boundary condition that influences this mechanism. We tested the model using time‐lagged supervisor–subordinate matched data. The results showed that moral disengagement mediated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 115 publications
3
11
0
Order By: Relevance
“…Lastly, while most studies have focused on the illegitimate task as a whole ( Semmer et al, 2010 ; Meier and Semmer, 2018 ; Wan et al, 2021 ; Zhao et al, 2021 ; Chen et al, 2022 ), it is valuable to examine the unreasonable task as a separate construct. This research has identified specific characteristics of the unreasonable task that activate the “cognitive-affect-behavior” chain reaction at the theoretical and data levels, which helps to reinforce the understanding of the illegitimate task as a whole and its sub-dimensions, and provides some reference for future research to clarify the nature and specific characteristics of illegitimate tasks’ sub-dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, while most studies have focused on the illegitimate task as a whole ( Semmer et al, 2010 ; Meier and Semmer, 2018 ; Wan et al, 2021 ; Zhao et al, 2021 ; Chen et al, 2022 ), it is valuable to examine the unreasonable task as a separate construct. This research has identified specific characteristics of the unreasonable task that activate the “cognitive-affect-behavior” chain reaction at the theoretical and data levels, which helps to reinforce the understanding of the illegitimate task as a whole and its sub-dimensions, and provides some reference for future research to clarify the nature and specific characteristics of illegitimate tasks’ sub-dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Negative affectivity (rated by employees) was measured through a 4-item scale adopted from Wong et al (2006) . Sample items include, “My job makes me dissatisfied,” “My job makes me unhappy,” “My job makes me troubled,” and “My job makes me miserable” [from strongly disagree (1) to strongly agree (4)], that was also adopted by Chen et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The conceptualization of NA as a momentary and transient state of negative emotions across certain situations and time ( Bohle and Tilley, 1993 ) in organizational research is particularly useful in capturing instant emotional reactions in response to effective experience. To exam in academics emotional reaction to CCB and its detrimental effect on performance, this research distinguished NA as a momentarily emotional response, referring to academics’ affect state at a given moment, such as feelings of disguise, anger or fear ( Wong et al, 2006 ; Chen et al, 2021 ). Such a state has unambiguous consequences on individual’s enthusiasm and initiatives, even leading to emotional exhaustion and physical burnout, that are of great relevance on the functioning of organizations.…”
Section: Development Of the Research Framework And Hypothesesmentioning
confidence: 99%
“…HR management ethics signifies the moral values and principles which monitor the behavior of organizations and individuals in managing their employees [75]. It involves the application of ethical principles and standards to various aspects of the employment relationship, including selection, recruitment, training & development, employee retention, performance management, and compensation & management [76].…”
Section: Human Resource Management Ethic -Hrementioning
confidence: 99%
“…Organizations prioritizing human resource management ethics typically enjoy a more engaged and productive workforce, lower employee turnover, and a more positive employer brand [73]. Ethical behavior in human resource management involves treating employees with respect, dignity, and fairness, providing equal employment opportunities to all, avoiding discrimination and harassment, protecting employee privacy and confidentiality, providing adequate training and development opportunities, and ensuring that compensation and benefits are fair and equitable [78,79]. Moreover, ethical human resource management entails honoring workers' rights to liberty of connection and collective negotiation and ensuring that they work in a safe and healthy workplace and have the opportunity to balance their personal and professional lives [80].…”
Section: Human Resource Management Ethic -Hrementioning
confidence: 99%